Private Label: o potencial impacto no mercado de medicamentos no Brasil - Ronaldo Raemy Rangel; Luan Vinicius Bernardelli; Paulo Rogério Alves Brene (Revista de Economia Mackenzie)
The objective of this article is to discuss how the release of private labels would change the dynamics of the industry with the eventual concentration of the retailer’s power in the medicines market. To this end, important theoretical aspects will be raised, based, for example, on Michael Porter’s theory (Five Competitive Forces and Value Chain). As a result of the study, private labels can obtain more favourable contractual conditions from manufacturers, increasing their market shares to the detriment of the competition and the consumer themselves. Although the study presents important elements for the discussion, it is necessary to expand the discussion regarding the link between private brands and abusive purchasing power, the trends observed, in the cases analysed, justify the concern with probable anti-competitive effects, especially in the market Brazilian medicines.